2019
DOI: 10.1108/aaaj-11-2017-3211
|View full text |Cite
|
Sign up to set email alerts
|

Strategizing in English hospitals: accounting, practical coping and strategic intent

Abstract: Purpose The purpose of this paper is to investigate the intricate ways in which accounting is implicated in the unfolding of strategizing in a pluralistic setting. The authors treat strategizing as a practical coping mechanism which begins in response to a problem and unfolds over time into an episode. This approach enables the authors to explore strategizing pathways and the ways they can mobilise accounting to advance from practical coping to explicit strategic intent. Design/methodology/approach The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 75 publications
(181 reference statements)
0
28
0
Order By: Relevance
“…A recent empirical study examined the practice of strategy for a group not widely researched in the literature; medical managers in directorate roles (Begkos et al, 2019). The research focused on the strategic planning approach taken in four English NHS hospitals.…”
Section: Strategy In Different Organisational Sectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent empirical study examined the practice of strategy for a group not widely researched in the literature; medical managers in directorate roles (Begkos et al, 2019). The research focused on the strategic planning approach taken in four English NHS hospitals.…”
Section: Strategy In Different Organisational Sectorsmentioning
confidence: 99%
“…Finally, engagement and training for medical managers in strategic planning endeavours would be advisable for policymakers due to the significant role medical managers play in healthcare strategic management. Begkos et al (2019) suggested further research in comparative cross-country analysis and further contextual research in this area. Although the primary focus of the research was on medical directors which gives valuable insight into hospital strategizing for this group, it would be beneficial to consider all individuals within a hospital environment and examine who, how and what each subgroup may contribute to strategy in this arena.…”
Section: Strategy In Different Organisational Sectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are knowledge experts with a varying level of competence and understanding of accounting and business processes, due to their limited management training (O'Riordan and McDermott, 2012). Yet, medical managers often engage with accounting to serve their diverse purposes via contesting, circumventing or conforming to accounting functions (Begkos et al , 2019, 2020) and extract financial value that benefits their business unit (Llewellyn et al , 2020). In addition, medical managers interact with various professional spaces in dynamic and unclear relationships characterized by great indecision and equivocality (Denis et al , 2001, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies have nevertheless considered strategy as their analytical focus. For example, some explored how accounting actors become involved with and use accounting devices in strategy-making (Roslender, 1995; Roslender and Hart, 2003; Whittle and Mueller, 2010), how the use of accounting in strategy-making can be seen as an everyday practice in response to environmental dynamics (Begkos et al , 2019; Chia and Holt, 2006) and how strategising takes place as a practical coping mechanism (Begkos et al , 2019). However, these studies paid little attention to how strategising can be situated within the evolutionary dynamics of neoliberal capitalism.…”
Section: Introductionmentioning
confidence: 99%